Rotate and Lean: Does Leaning toward the Target Direction Improves the Virtual Reality Navigation? - Hashemian, Abraham M.; Riecke, Bernhard E. (Second International Workshop on Models and Representations in Spatial Cognition, 2017)
Designing travel interfaces for Virtual Reality (VR) games can be challenging, because using standard travel techniques (e.g., joystick, mouse/keyboard) can contribute to unwanted side effects such as motion sickness and disorientation. In this study, we investigated if physical rotation and leaning-based translational motion cues can reduce these unwanted side effects. Fourteen participants followed an avatar in an unpredictable curvilinear path to compare Joystick with three other travel techniques, where in all of them the user sits on a chair and rotates physically to control their simulated rotation. However, each technique uses different approach for controlling the simulated translation: Real-Rotation, where users sit on a regular office swivel chair, and control their forward/backward and sideways translation by a Joystick; Swivel-Chair, where users sits on the same office swivel chair, but control their forward/backward translation by leaning the chair backrest forward/backward, while sideways head movements control sideway locomotion; NaviChair, where users sits on a sit/stand stool (SwopperTM) mounted on top of a Wii Balance board force plate, and control their forward/backward and sideways translation by shifting their weight toward the correspondent direction. Results indicate lower distance errors for the joystick compared to the NaviChair, but there were otherwise no significant differences between the joystick and other techniques. In a sense this could be seen as promising, in that the usability of the new interfaces approached or matched that of the well-trained joystick. Especially the Swivel-Chair seems promising and showed a trend towards lower motion sickness and higher sensation of self-motion, spatial presence, and intuitiveness than both the Joystick and Real-Rotation, while it had slightly higher distance error and lower ease of use, long time use and overall usability than the joystick. In sum, combining physical rotation with leaning-based translation for VR locomotion seems promising if their usability aspects can be further improved.
Keywords: Riecke; Riecke_2017; abraham-hashemian; bernhard-riecke; iat802; iat802_fall2016; leaning-based interfaces; motion-cueing; naviChair; poster; posterWithoutPaper; proj--motionCueingInterfaces; talkWithoutPaper